Modeling Inflammatory Bowel Disease by Intestinal Organoids - Di Giorgio, Cristina; Roselli, Rosalinda; Biagioli, Michele; Bordoni, Martina; Ricci, Patrizia; Zampella, Angela; Distrutti, Eleonora; Donini, Annibale; Fiorucci, Stefano (Recent Advances in Inflammation & Allergy Drug Discovery, 2023)
Inflammatory bowel disease (IBD) is a chronic and relapsing disease caused by a dysregulated immune response to host intestinal microbiota that occurs in genetically predisposed individuals. IBD encompasses two major clinical entities: ulcerative colitis (UC), limited to the colonic mucosa, and Crohn's disease (CD), which might affect any segment of the gastrointestinal tract. Despite the prevalence of IBD increasing worldwide, therapy remains suboptimal, largely because of the variability of causative mechanisms, raising the need to develop individualized therapeutic approaches targeted to each individual patient. In this context, patients-derived intestinal organoids represent an effective tool for advancing our understanding of IBD’s pathogenesis. Organoid 3D culture systems offer a unique model for dissecting epithelial mechanisms involved IBDs and testing individualized therapy, although the lack of a functional immune system and a microbiota, two driving components of the IBD pathogenesis, represent a major barrier to their exploitation in clinical medicine. In this review, we have examined how to improve the translational utility of intestinal organoids in IBD and how co-cultures of 3D or 2D organoids and immune cells and/or intestinal microbiota might help to overcome these limitations.
Keywords: Organoids